THE IMPORTANCE OF VIROLOGY AS A SCIENCE AND ITS CURRENT PRESSING ISSUES - Toshtemirova M. A. (Web of Journals Publishing, 2025)
The science of virology is one of the sciences with the most pressing problems today. This article includes the importance of the science of virology, the achievements and successes in the field of virology, including the origin of the science of virology and the development of this science.
Keywords: Virus, primary vaccines, DNA, RNA, capsid.